2021
DOI: 10.25122/jml-2020-0169
|View full text |Cite
|
Sign up to set email alerts
|

Low-level laser therapy in temporomandibular joint disorders: a systematic review

Abstract: Temporomandibular joint disorders (TMDs) encompass a wide array of ailments affecting the temporomandibular joint (TMJ), muscles of mastication, and the allied structural framework. Myofascial pain, internal derangement of the joint, and degenerative joint diseases constitute the majority of TMDs. TMDs usually have a multifactorial etiology, and treatment modalities range from conservative therapies to surgical interventions. Low-level laser therapy (LLLT) has evolved as an efficient non-invasive therapeutic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 56 publications
0
11
0
1
Order By: Relevance
“…In this study, a special probe from a laser device was used to perform intra-oral applications. The laser beam used in this study has a wavelength of 810 nm which penetrate further, so used to treat deeper-seated tissues as mentioned by Ahmad et al 73 The goal of this protocol was to reach almost all parts of the TMJ and surrounding muscles, particularly the lateral pterygoid muscle, which was linked to TMJ pain, pain with jaw movement and jaw restriction in patients with anterior disc displacement without reduction as shown in a previous study. 74 Although this study found a significant improvement in the studied aspects of TMD in all three treatment groups over all follow-up periods, a comparative analysis of all variables among groups revealed significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a special probe from a laser device was used to perform intra-oral applications. The laser beam used in this study has a wavelength of 810 nm which penetrate further, so used to treat deeper-seated tissues as mentioned by Ahmad et al 73 The goal of this protocol was to reach almost all parts of the TMJ and surrounding muscles, particularly the lateral pterygoid muscle, which was linked to TMJ pain, pain with jaw movement and jaw restriction in patients with anterior disc displacement without reduction as shown in a previous study. 74 Although this study found a significant improvement in the studied aspects of TMD in all three treatment groups over all follow-up periods, a comparative analysis of all variables among groups revealed significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there was a lack of definition of the treatment plan (laser irradiation) in several studies included. Recently, Ahmad et al 60 included 31 LT trials for the treatment of TMD, and the data were pooled according to LT dosage. Their meta-analysis showed a significant difference between the LT and PO groups; however, a high heterogeneity (I 2 = 90%) was exhibited.…”
Section: Discussionmentioning
confidence: 99%
“…Low-level laser therapy uses red or near-infrared light to relieve pain, reduce inflammation, and promote healing of chronic nonspecific low back pain, shoulder tendinopathy, and temporomandibular joint disorders 58–61…”
Section: Modalitiesmentioning
confidence: 99%